Restless Leg Syndrome and Sleep Quality in Lumbar Radiculopathy Patients - Ersoy Kocabicak; Murat Terzi; Kursad Akpinar; Kemal Paksoy; Ibrahim Cebeci; Omer Iyigun (Behavioural Neurology)
Background. To investigate the frequency of restless leg syndrome (RLS), sleep quality impairment, depression, fatigue, and sleep behavior disorder and to determine the effects of surgery on these parameters in radiculopathy patients resistant to conservative treatment. Methods. The present study included 66 lumbar radiculopathy patients, who were resistant to conservative treatment and had indication of surgery. Five different questionnaires were performed to assess depression (the Beck Depression Inventory (BDI)), sleep quality (the Pittsburgh Sleep Quality Index (PSQI)), fatigue (the Fatigue Severity Scale (FSS)), and presence of RLS and rapid eye movement sleep behavior disorder (RBD). The same questionnaires were also performed on a control group (n=61). Results. Of the radiculopathy patients, 68.1% had RLS and 92.4% had fatigue. Of the controls, 16.4% had RLS and 59% had fatigue. RBD was present in 8 (12.1%) patients and 3 (4.9%) controls. The PSQI revealed that sleep quality was impaired in 46 (69.7%) patients and 35 (57.4%) controls (P>0.05). The number of individuals having substantial depression according to the BDI was significantly higher in the patients than in the controls. Conclusions. There was a significant increase in the frequency of RLS, which was significantly decreased in the postoperative period in the radiculopathy patients.